Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.7553/84-2-1761
|View full text |Cite
|
Sign up to set email alerts
|

From planning to practice: an action plan for the implementation of research data management services in resource-constrained institutions

Abstract: Research data management (RDM) and its accompanying services and infrastructures are predominantly still in a state of infancy in many African countries and little is known about the RDM habits of the researchers from these areas. Our research showed that researcher RDM behaviour is similar across the globe, but our experience was that the will to implement formal RDM is not. Similarly, the responsibility for RDM implementation is not always clear. What is clear is that, although the library should not assume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(58 citation statements)
references
References 6 publications
7
42
0
Order By: Relevance
“…In the JISC study, only 33% of researchers were already sharing data while 35% expressed a willingness to share data in future. Patterton et al (2018) on the other hand determined that 12% of emerging researchers were not willing to share their data.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the JISC study, only 33% of researchers were already sharing data while 35% expressed a willingness to share data in future. Patterton et al (2018) on the other hand determined that 12% of emerging researchers were not willing to share their data.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…A study conducted by Onyancha (2016) showed that South Africa published close to 64% of all data published by Sub-Saharan African countries in the Data Citation Index hosted by Web-of-Science from 2009 to 2014. Despite this, there is currently scant evidence of the willingness, extent, concerns and practices of sharing data by South African researchers (Patterton et al 2018). The few studies conducted in South Africa in this area focus on data sharing practices of certain disciplines (Koopman & de Jager 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to a study conducted by Patterton et al (2018) in a number of research institutes in Sub-Saharan Africa found that experienced as well as emerging researchers made use of many different data types, both groups totalling more than 15 types. The most common data formats across both groups were spreadsheets, image files and textual data formats.…”
Section: Characteristics Of Research Datamentioning
confidence: 99%
“…According to Patterton et al (2018), there is a high willingness to share data with peers. This can be used to build confidence in researchers to promote seamless data sharing within teams before venturing outside.…”
Section: Sharing Of Research Datamentioning
confidence: 99%
“…Study authors evaluated data management service success through patron surveys (Read 2007;Choudhury 2013), attendance data for instructional sessions and consultations (Shen & Varvel 2013;Higman et al 2017), number of training sessions (Oliver et al 2019) and the growth of data in institutional repositories (Choudhury 2017). To plan the data management services, researchers' data practices were evaluated in two studies (Walters 2009;Patterton et al 2018). Lessons learned were described in two studies providing insights and challenges for creating a new service (Choudhury 2013;Ogier & Stamper 2018).…”
Section: Data Management Services (N=21)mentioning
confidence: 99%